1949
DOI: 10.1172/jci102068
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Induced Malaria, Acute Starvation and Semi-Starvation on the Electrophoretic Diagram of the Serum Proteins of Normal Young Men 1

Abstract: During the last ten years, the technique for the electrophoretic analysis of serum proteins, originally described by Tiselius (1), has been standardized and a large number of important conditions have been studied. Luetscher (2) has reviewed this work and pointed out that the common denominator of all disease processes studied has been a relative decrease in the albumin fraction. Both acute and chronic infections produce an increase in the alpha globulin fraction which is often accompanied by an increase in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1950
1950
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…This does not necessarily deny the importance of the concentration of the albumin fraction since in the present study neither the albumin nor the total protein concentration showed major changes at any time in these subjects (cf. Taylor et al [ 1 ] ); the range in the samples on which Figure 1 Bromsulfalein retention has been reported both during and after induced malaria (7,24,29); the phenomenon is similar in natural malaria (19). In natural P. falciparum malaria, Machella (31) found bromsulfalein retention during the febrile stage but not in the afebrile stage (remission), nor two or three days after the introduction of therapy (atabrine).…”
Section: Bilirubin and Urobilinogen In The Urinementioning
confidence: 90%
See 1 more Smart Citation
“…This does not necessarily deny the importance of the concentration of the albumin fraction since in the present study neither the albumin nor the total protein concentration showed major changes at any time in these subjects (cf. Taylor et al [ 1 ] ); the range in the samples on which Figure 1 Bromsulfalein retention has been reported both during and after induced malaria (7,24,29); the phenomenon is similar in natural malaria (19). In natural P. falciparum malaria, Machella (31) found bromsulfalein retention during the febrile stage but not in the afebrile stage (remission), nor two or three days after the introduction of therapy (atabrine).…”
Section: Bilirubin and Urobilinogen In The Urinementioning
confidence: 90%
“…For this purpose we have data on both the flocculation tests and the electrophoretic patterns of samples drawn when quinine was first administered to terminate the malaria. The details of the electrophoretic method have been reported previously (1). Figure 1 shows the correlation between the Hanger test and the percentage of the total protein fraction represented by gamma globulin.…”
Section: Bilirubin and Urobilinogen In The Urinementioning
confidence: 99%
“…Electrophoretic pattern shifts characteristic of other infectious diseases were observed in the plasma proteins (Taylor, Mickelsen and Keys [6]). …”
Section: -Ketosteroid Excretionmentioning
confidence: 99%
“…In general, there are few quantitative data on the physical deterioration produced by stress and almost none on the recovery process, the principal exceptions being the stresses of brief severe work, exposure to heat, and some of the stresses related to high altitude. To these may be added the stress of prolonged caloric undernutrition which we have recently studied in some detail (Keys et al [1] ; Henschel et al [2]; Simonson et al [3] ; Franklin et al [4]; Schiele and Brozek [5] ; Taylor et al [6]). …”
Section: Introductionmentioning
confidence: 99%
“…Liver enzymes are increased in malarial patients, and their level depends on the level of parasitemia (9). The level of liver impairment or damage may not be necessarily proportional to the degree of abnormality in the values obtained by the necessary tests (22), as the increase in the level of serum bilirubin may not be because of the malfunction of the liver, in which case it can also be determined by the rate of haemolysis of erythrocyte as a result of the malaria infection.…”
Section: Introductionmentioning
confidence: 99%